Strategic Design of Indigenous Community Economic Development in North Toraja Regency in Accelerating National Development - Randi Tangdialla; Lisa Kurniasari Wibisono; Iindarda S. Panggalo (Global Writing Academica Researching and Publishing, 2022)
Indigenous peoples are essential agents of change to achieve sustainable economic development. However, they remain part of the most disadvantaged and marginalized groups, untouched by the outside world. This encourages the government to focus economic development planning on indigenous peoples so that they can empower the community’s economy in various rural areas. This research was conducted to provide recommendations to local governments regarding the economic development of indigenous peoples in the North Toraja region so that they can be realized soon. The results of this study then conclude that there is strong cooperation between the Regional Government of North Toraja Regency and local customs (Tongkonan or To Parenge), recruitment of more experts to provide education and counseling to indigenous peoples in their respective customary territories, and regional development in strategic areas and better spatial planning to support the distribution and promotion of products developed by local indigenous peoples are solutions that can be considered by the Regional Government of North Toraja Regency in accelerating national development.